Perspektif Ekonomi Syariah Dalam Sistem Pembiayaan - Hanik, Nurma (Al Iqtishod: Jurnal Pemikiran dan Penelitian Ekonomi Islam, 2020)
The two main functions of banking are fundraising and channeling funds. The distribution of funds in conventional banks and those in Islamic banks has essential differences, both in terms of the name of the contract and the transaction. In conventional banking, this distribution of funds is known as credit, while in Islamic banking it is financing. In contrast to the definition of credit, which requires the debtor to return the loan by giving interest to the bank, financing based on the sharia principle of loan repayment with profit sharing is based on an agreement between the bank and the debtor. For example, financing under the buying and selling principle is intended to purchase goods, while those using the lease principle are intended to obtain services. The profit sharing principle is used for cooperative efforts aimed at obtaining goods and services at once. Financing is a very important activity because financing will provide the main source of income and support the continuity of the bank's business. Conversely, if the management is not good, it will cause problems and stop the bank's business.